Diverging EU health regulations: The urgent need for co ordination and convergence. (September 2018) - Negrouk, Anastassia; Lacombe, Denis; Meunier, Françoise
Highlights: The European Union has issued three key draft regulations critical to healthcare research. International trials often fall under the remit of multiple regulations. Smooth co-ordination between regulations is critical for healthcare development. Abstract: At the time of mayor breakthroughs in knowledge of molecular biology leading to change in design and conduct of innovative clinical research, there is a clear need for optimal co-operation at the EU level as well as with each Member States. The current legal framework for health research is developed and revised by several DGs dealing with clinical trials, data protection, in-vitro diagnostic tests and biomarkers. Also medical devices and advanced therapy directive / regulation have to be taken into consideration, all within a single trial/study. Such fragmentation of legal framework and national laws lead to several inconsistencies, wasting time and scarce resources of sponsors, whether academic or pharmaceutical industry and all involved parties are facing the complexity of current clinical research. Could we consider a single stop-shop for such initiative? Competitivity of European research is at stake and comprehensive coordination between all partners is crucial for the benefit of European citizens.